Migration in an ageing Europe: What are the challenges? - Jesús Crespo Cuaresma; Peter Huber; Doris A. Oberdabernig; Anna Raggl (WWWforEurope, 2015)
We use new migration modelling and projection techniques in order to quantify the effect of migration in the context of ageing societies in Europe over the forthcoming decades. Using new empirical results, data and projections of migration flows developed in the framework of the WWWforEUROPE project, we inform the policy discussion concerning the role of demographic change, inequality dynamics, labour market integration of migrants and the sustainability of public finances in the continent.
Keywords: E24; F22; H52; J62; 330; Academic research; Challenges for welfare system; Demographic change; Economic growth path; European economic policy; Full employment growth path; Labour markets; Migration; Policy options; Sustainable growth; Welfare state